Socialization of Corruption Prevention Through Anti-Corruption Education in the State Elementary School 06775 Medan Johor - Akmal; Elwardi Hasibuan (PT Katersi Minar Permata, 2024)
Corruption is a problem that is very detrimental to the Indonesian state. Corruption has a negative impact on government, hampers development, and harms society directly or indirectly. One of the efforts to prevent corruption is to provide anti-corruption education to children from an early age in the school environment. Based on observations at State Elementary School 06775 Medan Johor, there are several problems as follows: 1) Many students do not know what corruption is. 2) Lack of knowledge about corruption so that students do not know that they have committed corruption. Therefore, it is necessary to socialize students to know the meaning, impact and examples of corruption. Anti-corruption socialization through anti-corruption education in elementary schools is carried out with the aim of increasing students' understanding of corruption, developing anti-corruption attitudes and values, and creating a corruption-free school environment. The method used was counseling to students, teachers and school staff. The results of this socialization show that students have a better understanding of corruption, know various corrupt practices, and understand the negative impact on society and the country. Anti-corruption socialization through anti-corruption education at State Elementary School 06775 Medan Johor has yielded positive results. Students' understanding deepened, attitudes and values towards corruption were formed, and a corruption-free school environment was created. Through this effort, it is hoped that the young generation involved can become agents of change to fight corruption and build a more honest, fair and quality society. With such positive results, it is important to maintain sustainability by integrating the program into the school curriculum and activities.